The circular economy from the perspective of islamic economics: Advancing a sustainable halal production model - Triana Septiani; Iftitaha Fadhila; Monasdir; Kresna Bayu Adelta (Halal Studies and Society, 2026)
This study aimed to analyze the integration of circular economy concepts with the principles of Islamic economics to formulate a sustainable halal production model. A Systematic Literature Review (SLR) method was adopted to examine a wide range of scholarly publications related to the circular economy, the halal industry, and maqasid al-shariah to identify opportunities for conceptual integration. The results show that despite the significant potential of the halal industry to adopt circular economy principles, the implementation remained partial and was not systematically integrated within a Shariah-based framework. Based on the synthesis of the literature, this study proposed a conceptual framework, referred to as the Circular Halal Production Model (CHPM). This framework consisted of seven core components, namely normative foundations, halal-circular product design, value-retention-based production, circular halal distribution and logistics, sustainable halal consumption, Shariah-compliant value loops, and value regeneration. The model conceptually connected resource efficiency and waste reduction with the principles of halalan tayyiban and maqasid al-shariah. Accordingly, the study offered a conceptual contribution to the development of Islamic economics literature and showed opportunities for future empirical investigation on sustainable halal production systems.